Psychometric properties of the perceived stress scale (PSS‐10) among pregnant women in China - Zhang, ZiYang; Wang, Qingzhi (Frontiers in Psychiatry, 2024)
BackgroundPregnancy, a transformative phase, is often fraught with considerable psychological stress. Within the context of Chinese culture, characterized by intricate family dynamics, societal expectations, and deeply rooted traditional beliefs, the manifestation of stress during pregnancy may present with distinct nuances. The adaptation and validation of the Perceived Stress Scale (PSS-10) for the Chinese context are pivotal for a nuanced understanding and effective intervention for the stressors encountered by pregnant women in China.MethodsThis study enrolled a cohort of 990 pregnant women who completed both the PSS-10 and the Chinese Mental Health Scale (CMHS). The internal consistency reliability was assessed using Cronbach’s α and McDonald’s omega. The construct validity was explored through Exploratory Factor Analysis (EFA), while Confirmatory Factor Analysis (CFA) was utilized to validate the scale’s structural integrity. Criterion-related validity was established by correlating PSS-10 scores with CMHS scores, thereby assessing the scale’s convergent and discriminant validity.ResultsThe result demonstrated PSS-10 had robust internal consistency, with Cronbach’s α coefficients and McDonald’s omega (Composite reliability) were more than 0.70 for the scale and its constituent sub-factors. EFA and parallel analysis revealed two salient factors with eigenvalues surpassing 1.0, which accounted for 60.58% and 63.22% of the variance among the second and third trimester samples, respectively. The CFA confirmed the two-factor model’s congruence with the PSS-10’s structure in both sub-samples, with excellent model fit indicated by the fit indices: Standardized Root Mean Residual (SRMR) below 0.08 and both Comparative Fit Index (CFI) and Goodness of Fit Index (GFI) above 0.90. Additionally, the correlation analysis with CMHS scores substantiated the PSS-10’s concurrent validity.ConclusionThe PSS-10 exhibits commendable psychometric properties, rendering it a pertinent and reliable instrument for assessing perceived stress among pregnant women in China. This validation underscores the PSS-10’s utility in psychological research and clinical practice pertaining to Chinese pregnant populations.